The Wealth-Age Relation among the Aged - Mirer, Thad W. (American Economic Review, 2016)
Aged people face the problem of allocating over the rest of their lifetimes the wealth that they have accumulated during their working years. This problem is fairly complex, because they are uncertain about the dates of their death and because they may wish to use their wealth to finance general consumption, or hold it to meet emergencies, leave estates, or maintain power or status. Whether skilled at dynamic programming or not, aged people effectively do make these decisions. What are the results? Some studies of the entire lifetime pattern of saving and wealth tend to support the simple life cycle model, in which the aged use up their wealth to help finance consumption. Harold Lydall, for example, found saving rates to increase and then decrease with age in the whole population and to be negative for the group aged 65 and over. Guarded support for the theory was found by Franco Modigliani and Albert Ando in Britain and by Dorothy Projector in the United States. More recently, A.F. Shorrocks examined the lifetime pattern of wealth holding in estate-tax data for a single cohort and found the hump pattern that is characteristic of life cycle saving. Other evidence on wealth holding runs contrary to this, however. In a study of estate-tax returns in Washington, D.C., James D. Smith found that wealth increased with age among the aged, after controlling for other demographic variables. Examining national estate-tax data, John Brittain found wealth to increase with age in the United States and A. B. Atkinson and A. J. Harrison reported the same pattern in England and Wales. In a sample of (TIAA) annuity recipients analyzed by James Mulanaphy, over half reported that their total savings had increased during retirement and another quarter reported that their savings had remained about the same. In this paper, I examine wealth holding patterns among aged married couples, using survey data representing the entire aged population of the United States in 1968. The statistical analysis serves as a test of the hypothesis that emerges from life cycle theory and provides some further exploration into the economic behavior of the aged. I find that the aged tend to increase their wealth over time.